(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2017)
Tuberculosis of paranasal sinuses is very rare. It is usually secondary to pulmonary Tuberculosis. Among the Paranasal sinuses, maxillary sinus is the most common to be involved by tuberculosis. Frontal sinus Tuberculosis is very rarely seen. We report a case of extra-pulmonary Tuberculosis of frontal sinus presenting as mucocele in a 40 year old female who presented with a painless swelling. Computed Tomographic scan of Paranasal Sinuses revealed it to be a mucocele but Fine Needle Aspiration Cytology clinched the diagnosis. It was managed conservatively by Anti Tubercular Treatment. SAARC J TUBER LUNG DIS HIV/AIDS, 2017; XIV(1), page: 46-48